2010
DOI: 10.1038/jes.2009.75
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fine particles and smoking activity in a statewide survey of 36 California Indian casinos

Abstract: Despite California's 1994 statewide smoking ban, exposure to secondhand smoke (SHS) continues in California's Indian casinos. Few data are available on exposure to airborne fine particles (PM2.5) in casinos, especially on a statewide basis. We sought to measure PM2.5 concentrations in Indian casinos widely distributed across California, exploring differences due to casino size, separation of smoking and non-smoking areas, and area smoker density. A selection of 36 out of the 58 Indian casinos throughout Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 33 publications
(49 reference statements)
6
40
1
Order By: Relevance
“…The observed percent of active smokers in the casino is similar to the active smoker prevalence reported in 36 California Indian casinos of 11 % (range, 5–25 %) [9], and the prevalence reported in 7 Reno casinos of 9.3 % (range, 7–12 %) [6]. Klepeis et al [10] found a somewhat lower active smoker proportion of 7 % (range, 5–10 %) in 11 southern California casinos.…”
Section: Discussionsupporting
confidence: 77%
“…The observed percent of active smokers in the casino is similar to the active smoker prevalence reported in 36 California Indian casinos of 11 % (range, 5–25 %) [9], and the prevalence reported in 7 Reno casinos of 9.3 % (range, 7–12 %) [6]. Klepeis et al [10] found a somewhat lower active smoker proportion of 7 % (range, 5–10 %) in 11 southern California casinos.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we were able to identify few studies systematically exploring population disparities related to SHS exposure, smoke-free policies and related health effects in casinos. In particular, we found few studies that assessed SHS exposure in tribal casinos 15 50. It would be helpful for future research to address these gaps in the existing literature.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study of 36 tribal casinos found that PM 2.5 levels in non-smoking gaming areas in smoking-permitted casinos averaged 22 μg/m 3 (43 μg/m 3 for areas with no separation from smoking gaming areas, 20 μg/m 3 for areas with semiseparation and 7.9 μg/m 3 for areas with complete separation), compared with 5.4 μg/m 3 in a smoke-free casino and a 7 μg/m 3 level measured outdoors using the same method 15. Similarly, a study assessing air quality on casino gaming floors and in casino restaurants after implementation of Nevada's 2006 Clean Indoor Air Act found that partial smoking restrictions had limited effect 18.…”
Section: Impact Of Smoke-free Laws On Casino Air Qualitymentioning
confidence: 88%
“…[16][17][18] Casino workers and patrons are exposed to high levels of secondhand smoke, including carcinogens and fine particulate matter associated with cardiovascular disease (PM 2.5 ). [18][19][20][21][22][23] Air quality studies demonstrate that non-smoking areas within casinos, without physical barriers, provide no protection from secondhand smoke exposure; non-smoking areas, partially separated from smoking areas, provide minimal protection and smoke-free areas, completely separated from smoking areas by physical barriers, provide good protection. 18 21 22 Studies show that a small portion of actively smoking casino patrons (7-12%) are responsible for the high levels of secondhand smoke found in casinos and ventilation systems are not effective at removing secondhand smoke.…”
Section: Secondhand Smoke Exposure Problemmentioning
confidence: 99%